2017
DOI: 10.20525/ijfbs.v6i1.650
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Liquidity on Profitability in Banking Sectors of Iraq

Abstract: This study examines the influence of liquidity on the profitability of Iraqi commercial banks. Five banks based in Iraq namely: North bank, Iraqi Islamic bank, Sumer bank, Dar Es-Salam bank and Babylon bank randomly selected and analyzed for the current study over the period 2005 to 2013. Moreover,  annual reports of these banks have studied and the main ratios of profitability and liquidity were calculated. These reports are available at Iraqi Stock Exchange site. The variables that were identified as indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 5 publications
1
16
0
3
Order By: Relevance
“…The results of the study on the effect of bank liquidity on the profitability of commercial banks showed that an effect of bank liquidity (liquidity ratio, legal liquidity ratio, employment ratios) on the ROA of Jordanian commercial banks for the period 2013-2017. This was confirmed by the study of (Ibrahim, 2017) which was contradicted with the study of (Rahma and Sereen, 2009). In addition, it was found that the effect of bank liquidity (liquidity ratio, legal liquidity ratio, employment ratios) on the return on equity of Jordanian commercial banks for the period 2013-2017.…”
Section: Discussionmentioning
confidence: 80%
“…The results of the study on the effect of bank liquidity on the profitability of commercial banks showed that an effect of bank liquidity (liquidity ratio, legal liquidity ratio, employment ratios) on the ROA of Jordanian commercial banks for the period 2013-2017. This was confirmed by the study of (Ibrahim, 2017) which was contradicted with the study of (Rahma and Sereen, 2009). In addition, it was found that the effect of bank liquidity (liquidity ratio, legal liquidity ratio, employment ratios) on the return on equity of Jordanian commercial banks for the period 2013-2017.…”
Section: Discussionmentioning
confidence: 80%
“…The studies of Pimentel et al (2005) and Hirigoyen (1985) argue that due to low liquidity, firms resort to loans which impact profitability and this works like a vicious cycle. Ibrahim (2017) and Pimentel et al (2005) find a positive relationship between liquidity and financial performance that differs from the finding of Lamberg and Vålming (2009) which finds no relationship. For this research, this aspect is measured using current ratio as used by Makris (2016) and Ayaydin and Karaaslan (2014).…”
Section: Liquidity and Profitabilitymentioning
confidence: 77%
“…Liquidity has significant impact on profitability (Bibi & Amjad, 2017). The result of previous study found that profitability have negative and significant impact on financial distress (Moch et.al, 2019; Masdupi et al, 2018;Ibrahim, 2017).…”
Section: Literature Reviewmentioning
confidence: 94%